A critical review on mechanically alloyed high entropy alloys: processing challenges and properties. (1st May 2022) - Kumar, Akshay; Singh, Alok; Suhane, Amit
Abstract: High entropy alloys are an innovative class of materials for a wide range of industrial applications due to their competitive properties such as improved mechanical properties, superior wear resistance characteristics, and excellent corrosion behavior, which are widely desired for a variety of applications considering several attributes such as economical, eco-friendly and safety. Thus, the quest for high-performance materials with exceptional properties is an unfading research topic for researchers, academia, and metallurgical scientists. HEA presents a novel alloy design idea focused on multi principal elements, a huge compositional space, and more opportunities to develop diverse alloys with exceptional properties. As universally acknowledged, the immense potential in compositions, microstructures, and properties has sparked a great interest in this field. Researchers primarily focused on equimolar HEAs, but the precedent eventually shifted to non-equimolar alloys. As the investigation over HEAs progressed, four core effects were identified as the most important aspects in enabling the distinct characteristics. Mechanical alloying (MA), followed by the sintering approach, has piqued the interest of all researchers focusing on HEA development. As a result, the main intent of this study is to examine mechanically alloyed HEAs critically for mechanical properties, tribological behavior, corrosion behavior, and functional properties. Furthermore, the predominant challenges and their conceivable prospects are also deliberated that offer novelty to this review article.